1991
DOI: 10.1136/hrt.66.5.351
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor in plasma: a novel risk factor for recurrent myocardial infarction and death.

Abstract: Objective-To evaluate as predictors of reinfarction and mortality tissue plasminogen activator antigen and activity before and after venous occlusion, plasminogen activator inhibitor, von Willebrand factor, and established risk factors.Design-Prospective study with a mean observation time of 4 9 years.Setting-Secondary referral centre, the Department of Internal Medicine, University Hospital of Umea.Patients-123 consecutive survivors of myocardial infarction under the age of 70 years.Main outcome measures-Rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
184
5
7

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(219 citation statements)
references
References 26 publications
23
184
5
7
Order By: Relevance
“…Although the causative mechanism remains to be elucidated, our findings may be explained in part by the occurrence of pulmonary congestion secondary to acute myocardial infarction, because it has previously been pointed out that plasma vWF concentrations are increased in patients with heart failure regardless of the underlying heart disease. [27][28][29][30] In accordance with this hypothesis, plasma vWF levels have been shown to be correlated with pulmonary capillary wedge pressure. 31 In the present study, the highest vWF plasma levels were demonstrated in patients with delayed blood flow in the main trunk of the left coronary artery, resulting in severe pulmonary edema.…”
Section: Discussionmentioning
confidence: 50%
“…Although the causative mechanism remains to be elucidated, our findings may be explained in part by the occurrence of pulmonary congestion secondary to acute myocardial infarction, because it has previously been pointed out that plasma vWF concentrations are increased in patients with heart failure regardless of the underlying heart disease. [27][28][29][30] In accordance with this hypothesis, plasma vWF levels have been shown to be correlated with pulmonary capillary wedge pressure. 31 In the present study, the highest vWF plasma levels were demonstrated in patients with delayed blood flow in the main trunk of the left coronary artery, resulting in severe pulmonary edema.…”
Section: Discussionmentioning
confidence: 50%
“…A recent prospective study suggests that dysfunction of vascular endothelium as indicated by raised vWF may be a link between albuminuria and atherosclerotic cardiovascular disease in NIDDM [37]. Furthermore, a high concentration of vWF is an index of increased risk for reinfarction and mortality in diabetic and non-diabetic survivors of myocardial infarction [40]. Other markers of generalized vascular endothelial cell damage, e. g. raised plasma thrombomodulin concentration have also been demonstrated in NIDDM patients with microand macroalbuminuria [41].…”
Section: Discussionmentioning
confidence: 99%
“…A suggested mechanism for the association between ®brinogen, CRP and cardiovascular disease (CVD) is in¯ammation, since both proteins are acute phase proteins and their plasma levels may re¯ect systemic in¯ammation or atherosclerosis of the vascular wall. Other markers for the risk of cardiovascular events that are associated with in¯ammation, are the haemostatic factors Von Willebrand Factor (vWF Thompson et al, 1995;Jansson et al, 1991), plasminogen activator inhibitor-1 (PAI-1 Hamsten et al, 1987), activated factor VII (FVIIa Meade et al, 1986;Miller et al, 1994) and urokinase-type plasminogen activator (u- PA Munkvad et al, 1990). vWF and PAI-1 are also markers for endothelial function.…”
Section: Introductionmentioning
confidence: 99%